Media Bias and Tax Compliance: Experimental Evidence - Miloš Fišar; Tommaso Reggiani; Fabio Sabatini; Jiří Špalek (Masaryk University, Faculty of Economics and Administration, 2020)
We study the impact of media bias on tax compliance. Through a framed laboratory experiment, we assess how the exposure to biased news about government action affects compliance in a repeated taxation game. Subjects treated with positive news are significantly more compliant than the control group. The exposure to negative news, instead, does not prompt any significant reaction in respect to the neutral condition, suggesting that participants perceive the media negativity bias in the selection and tonality of news as the norm rather than the exception. Overall, our results suggest that biased news act as a constant source of psychological priming and play a vital role in taxpayers' compliance decisions.
Keywords: C91; D70; H26; H31; 330; Tax compliance; media bias; taxation game; laboratory experiment